Pengaruh Pembelajaran Daring Berbasis Whatsapp Dan Metode Pemberian Tugas Terhadap Motivasi Belajar Siswa di SMA Negeri 1 Kefamenanu - Hendrik, Yandri Yusuf Cornelis; Pingak, Elisabeth M.; Purnomo, Catur (Jurnal Ilmiah Mandala Education (JIME), 2023)
The online learning implementation during the COVID-19 pandemic by using WhatsApp and assigning assignments as one of the methods used by teachers in providing material. The purpose of the study is to determine the effect of WhatsApp-based online learning and assignment methods on student learning motivation in PAK subjects at SMA Negeri 1 Kefamenanu. The research method is Quantitative Method. All students who are Christian is the population of this study.Total of 56 samples using proportional random sampling technique. The results showed that the online learning variable via WhatsApp has a positive and significant influence on students' learning motivation. The regression coefficient of 0.377 is positive with a t-count value of 3.156. The assignment method variable has positive and significant effect on students' learning motivation. The regression coefficient of 0.287 is positive with a t-count value of 2.130. The online learning variable and the assignment method simultaneously have a simultaneous effect on the F value of 4.343. While the resulting significance value is 0.018 which is smaller than 0.05 and contributes 14.1% to students' learning motivation.